International timeshare contracts, some issues raised in the light of Spanish jurisprudence - Sabido Rodríguez, Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The proliferation of timeshare contracts in the market is a reality in view of the high number of pronouncements by Spanish judicial bodies in recent times. Its analysis, which focuses on the object of this study, will allow to highlight the main difficulties derived not only from the complexity of this figure but also from the internationalization of the legal relationships to which it is the subject. Focusing on the problems relating to the determination of international judicial competence, we will make a brief reference to passive legitimation and, due to its connection, to the designation of the applicable law.
Keywords: time-share contracts; international jurisdiction; applicable law; procedural legitimacy; protection of consumers